From the return of Mercedes Sosa to the assumption of Raúl Alfonsín: emerging actors in Argentine folklore (Revista Argentina de Musicología, 2019)
The decline of the military government after the defeat in the Malvinas War opens a new stage in the folklore genre: the silencing of the last years to the zone of the field linked to the “militant song” is broken.In the context of the “transition to democracy”, Mercedes Sosa —widening her repertoire— and other “consecrated” referents linked to the “militant song” return to act and edit discs, enabling and legitimizing productions of emerging actors with proposals of renovating intention.In this sense, we highlight the discs of Antonio Tarragó Ros (1982), Chany Suárez (1982), Suna Rocha – Raúl Carnota (1983) and Teresa Parodi (1983). Following the social-discursive model proposed by Claudio Díaz, in this paper we propose an analysis of these four productions
Keywords: Folklore; Argentina; Transition to Democracy